Mistakes we never made [large type] - Brown, Hannah (Hannah Kelsey), 1994-; Larrabee, Emily (THORNDIKE PRESS LARGE PRINT Romance, 2024)
"Emma Townsend can sum up her situationship with hot-as-hell romantic red flag Finn Hughes in one word: almost. They almost dated in high school. They almost hooked up after college. They almost took things too far one magical night. Their whole story is one series of "almosts" and "nearlys," and now they just kind of can't stand each other. Like, at all. But this weekend, one of their mutuals is getting married . . . and Emma and Finn will have to pretend they don't remember how disastrous it was the last time they were in a room together. Emma's doing a stellar job of playing it cool--until the bride goes missing. Now, with two days before the wedding, Emma and Finn are hitting the road in a sweet vintage sports car in hopes of salvaging someone else's happily-ever-after. Yet somewhere between Emma's breakfast burrito throw down, a high-stakes kayak chase (it can happen), and an outrageous Vegas detour, these sworn enemies are crossing more than just state lines. As old feelings spark once more, Emma begins to question whether risking your heart is ever really a mistake"--